Molecular recognition using fluorescence spectroscopy - Sennaroğlu, Müge (My University, 2006)
MOLEKÜLER ALGILAMANIN FLORESANS SPEKTROSKOPİSİ İLE İZLENMESİ Moleküler baskılanmış jel içerisindeki hedef molekülün absorpsiyonunun yüksek hassasiyetle izlenebilmesi amacıyla floresans tekniği kullanılmıştır. Floresans prob dahil edilmemiş 3-amino benzoik asit baskılanmış, akrilik asit esaslı, sistemler hazırlanmış ve değişik çapraz bağlayıcı/ monomer (68.37, 60, 50, 40) oranlarının hedef molekül absropsiyonu üzerindeki etkileri test edilmiştir. Bunun için, hazırlanan polimerik sistemler 3-amino benzoik asit ve 2-hidroksi-1-naftonoik asit içeren çözeltilere daldırılarak, azalan 3-amino benzoik asit miktarları HPLC ile takip edilmiştir. En yüksek absorpsiyon, çapraz bağ/ monomer oranının 68.37 olduğu polimerik sistemlerde tespit edilmiş ve optimum oran olarak belirlenmiştir. Özel ESIPT reaksiyonları gerçekleştiren ve bunun sonucu olarak belirgin çift band yayılımı oluşturan 3-HF türevleri, 2-hidroksi-asetofenon ve paraformaldehit reaksiyonundan yola çıkılarak dört aşamada sentezlenmiştir. Son aşamada, flavon molekülün, baskılanmış sisteme dahil edilebilmesi amacıyla yapıya HEMA takılmış ve vinil gruplu 3-HF türevi bu şekilde elde edilmiştir. Sentezlenen ürünlerin saflıkları ve reaksiyonlardaki değişimler TLC (İnce Tabaka Kromatografisi) ,1H-NMR (Proton Nükleer Magnetik Rezonans) ve MASS (kütle spektroskopisi) kullanılarak kontrol edilmiştir. Absorpsiyonlardaki değişimler ve 3-HF lerin farklı polaritelerdeki floresans özellikleri florimetri yöntemi ile izlenmiştir. Farklı polarite ortamları, çözeltiye su ilave edilerek ( %0-%17,9) oluşturulmuştur. Prob’un N* band pozisyonu ve şiddetinde artış gözlemlenirken, T* bandı sabit kalmıştır. Vinil gruplu 3-hidroksi flavonların dahil edilmesiyle hazırlanan cAMP baskılanmış polimerik yapıdan hedef molekül, cAMP, sokslet ekstraksiyonu ile uzaklaştırılmıştır.Bunun sonucu olarak hidrojel içerisinde, moleküler hafızaya sahip, cAMP şeklini almış, boşluklar oluşmuştur. Jeller sulu ortamda cAMP, 3-amino benzoik asit ve 2-hidroksi-1-naftonoik asit içeren çözeltiye daldırılarak floresans ölçümleri alınmış ve en iyi hedef molekül absorpsiyonunun 15 gün bekletilmiş örnekte gerçekleştiği gözlemlenmiştir. Ayrıca, yüksek polarite nedeniyle N* ve T* bandları birleşerek 400-650 nm aralığında tek band yayılımı göstermişlerdir.

MOLECULAR RECOGNITION USING FLUORESCENCE SPECTROSCOPY A combination of molecular imprinting and flourescence techniques were employed for the recognition of template molecule inside the hydrogel in high sensivity. Imprinted systems including no fluorescence probe were prepared using 3-aminobenzoic acid as a template molecule and different crosslinker/ monomer ratios (68.37, 60, 50, 40 ) were tested to investigate the effect of crosslinker/ monomer ratios on their molecular recognition capability. For this purpose, different compositions of polymers were prepared and plunged into a solution containing 3-amino benzoic acid and 2-hydroxy naphtonoic acid. The decrease in the 3-amino benzoic acid concentration was followed by HPLC and optimum crosslinker/ monomer ratios was determined. The highest template molecule recognition capability was obtained at the crosslinker/ monomer ratio of 68,37. The 3-HF derivatives realising special ESIPT reactions, resulting in prospective two bands, were synthesized. This was possible through five step reaction, starting from 2-hydroxy acetophenone and paraformaldehyde reaction. The vinylated 3-HF derivative was formed by attaching 2-hydroxyethylmethacrylate (HEMA) to final flavone melecule in order to insert it into the polymeric imprinted structure. Purity of products and progress of the reactions were controlled by TLC (thin layer chromatography), 1H-NMR (Proton Nuclear Magnetic Resonance) and MASS (mass spectroscopy). Fluorimetry was used for exploring the variations of absorption and fluorescence properties of 3-HF with the change in environment polarity. Different percentages of water ( % 0 - % 17,9) was added in order to change the environment polarity. It was observed that there were distinct increases at N* band position and intensity of probe molecule, with increasing water percentages while T* band remained constant. The imprinted systems were prepared by incorporation of cAMP and the synthesized vinylated 3-HF derivative into the hydrogels. The cAMP was removed by extraction, which lead to the formation of cavities in the shape of cAMP molcules inside the hydrogel. The gels so obtained were immersed into a solution of cAMP, 3-amino benzoic acid, 2-hydroxy-1-naphtonoic acid, methanol and water. Results indicated that interactions outside the gel were more intense than those inside the gel. The fluorescence measurements taken after 15 days presented the best template molecule recognition capability. It was also observed that N* and T* bands have combined to yield one band between 400 and 650 nm because of highly polar medium.
Keywords: Kimya; Moleküler Baskılanma